Hubungan Faktor Ekternal Terhadap Keberhasilan UMKM Kuliner Dalam Menghadapi Persaingan Industri: The Relationship of External Factors to the Success of Culinary MSMEs in Facing Industrial Competition (A Case Study of Culinary MSMEs in Makassar City) - Suryani, A. Irma; Retno Dwi Astuti, Diah; Syafri, Muhammad; Rahim, Abd; Astuty, Sri (Universitas Sumatera Barat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in accessing capital and dealing with complex regulations, both of which hinder their growth and development. This study aims to identify the external factors that influence the success of culinary MSMEs in facing industrial competition and to analyze how these external factors relate to their competitive success. The research employs a descriptive quantitative approach, with data collected through questionnaires distributed to 99 culinary MSME owners. The results of the analysis indicate that there is no significant relationship between the legal framework and access to finance and the competitive success of culinary MSMEs. However, human resource capacity demonstrates a significant relationship with competitive success. The findings show that human resource capacity (HRC) presents a significant difference between observed and expected values.